LEADERSHIP IN AN EFFECTIVE TEAM - Kania, Raden; Haerani, Anggi; Noviani, Lona; Kusuma, Yudha (Universitas Banten Jaya, 2024)
Leadership is an important central point in an organization. To be a good leader requires a variety of knowledge, experience, and skills in various things. This article discusses effective leadership in teams. Leaders chosen in an organization or team are required to have the ability in various ways, especially in organizing team members to achieve goals or goals effectively and efficiently, encouraging each team member to be able to make their best contribution to the organization, company, or institution even in the team. The purpose of writing is to know about effective leadership in a team and to achieve goals effectively and efficiently. The method of writing this is to conduct a literature review from various printed sources and various other sources of scientific information. Based on the observations obtained, successful leadership is influential leadership, transformative leadership, and leaders who can overcome dynamics in the team. Some things that affect leadership effectiveness include; the relevance of leadership style, leadership qualities, leadership qualities, and good teamwork.